Часовая коллекция Цяньлуна (1736–1795): первое собрание европейского искусства в Китае - Neglinskaya, M.A. (Искусство Евразии, 2020)
Many of European clocks in the Beijing’s Palace Museum (Gugong) were made in second half of the 18th century, by the Qing Emperor Qianlong’s governing (1736–1795), when an exotic “Chinese style” (chinoiserie) in the decorative arts was at its height. The research methodology proposed below, which combines art history and cultural analysis, allows us to see, that the Palace Collection’s mix determined evolution of the clock’s industry in China and some European lands, who took part in the international clock and watch market. In forms and decor of Chinese clocks the 18th century were reflected the change of European market. Together with western mechanical clock, being at the same time scientific device and work of decorative art, the European styles system was by ritual participation admitted in China. В статье показано, что западная часовая коллекция Цяньлуна (1736–1795), явившаяся первым в империи Цин (1644–1911) собранием произведений европейского искусства, связана с художественным рынком и феноменом шинуазри. Предложенная ниже методология, сочетающая искусствоведческий и культурологический подходы, позволяет увидеть, что состав этой коллекции повлиял на развитие производства механических часов в самом Китае и западных странах — участницах международного рынка искусств XVIII века. Собирательство механических хронометров в государстве Цин было обусловлено ритуализацией часов, устранившей проблему дуализма китайского и западного начал в цинской культуре и искусстве.